Establishment of sugar palm (Arenga pinnata) shoot from zygotic embryo in MS medium sumpplemented with different concentrations of benzylaminopurine - Nur Suraya Abdullah,; Noorshilawati Abdul Aziz,; Asmah Awal, (Malaysian Society of Applied Biology, 2015)
Arenga pinnata is one of the potential crops which provide a great number of products such as ethanol, starch and fiber. This plant usually propagated by seed but its seed growth is unpredictable and may take more than one year to germinate. The study was conducted with aim to obtain plantlets through initiation of half matured fruits of sugar palm. Zygotic embryo obtained from fresh half matured fruits were directly excised and cultured into MS free-hormone medium and MS medium treatments supplemented with 6-benzylaminopurene (BAP) at concentrations 0.1, 0.5, and 3.0 mg/L. Zygotic embryo cultured on MS0 served as control treatment. The results of the study indicated that MS medium supplemented with 0.5 mg/L BAP shows no regeneration of explant, shoot and radicle after four weeks culture. However, although after 8 weeks culture 59.5% explant was regenerated with increased radicle size, but the shoot emergence was only observed after 24 weeks culture. Meanwhile, regeneration of zygotic embryos in MS medium hormone-free resulted in highest percentage of plantlets produced (90%) with production of one shoot, longest radicle (4.5 cm) and longest plantlet length (6.0cm) as compared with other treatments. In vitro seedling was successfully developed after 32 weeks culture.